Diffusion (DOSY) 1H NMR as an Alternative Method for Molecular Weight Determination of Poly(ethylene furanoate) (PEF) Polyesters. Issue 1 (11th November 2016) - Rosenboom, Jan‐Georg; Roo, Jonathan De; Storti, Giuseppe; Morbidelli, Massimo
Abstract : Poly(ethylene furanoate) (PEF) is a promising 100% biomass‐derived alternative to poly(ethylene terephthalate) (PET), but challenges all solution characterization methods due to its insolubility in most common solvents. Diffusion (DOSY) 1 H NMR can be an alternative, reliable and fast method to analyze molecular weights of PEF polyesters. Calibration with PET standards yields excellent agreement of DOSY predictions with the absolute M n and M w values obtained via size exclusion chromatography equipped with multi‐angle light scattering detector in the range of commercial relevance ( M w < 100 000 g mol −1 ). Mean square displacement analysis shows unhindered molecular diffusion for all tested concentrations (from 0.4 to 30 mg mL −1 ). The DOSY procedure can be optimized toward shorter analysis times (down to 1 min) and a more straightforward implementation, making it a powerful and fast tool for molecular weight analysis in the laboratory as well as in industrial process applications. Abstract : In this work, diffusion (DOSY) 1 H NMR is explored as an alternative, reliable, and fast method to analyze molecular weights of poly(ethylene furanoate). Excellent agreement of DOSY predictions with the absolute number‐ and weight‐average molecular weights from light scattering and optimized DOSY analysis times (down to 1 min) underline the attractiveness of DOSY as a powerful and fast tool.